2020
DOI: 10.1007/s13577-020-00377-z
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the treatment of osteoarthritis with umbilical cord stem cells

Abstract: Osteoarthritis is a chronic degenerative joint disease with an incidence of 81% among people aged over 65 years in China. Osteoarthritis significantly decreases the quality of life of patients, causing physical and psychological damage and posing a serious economic burden. Clinical treatments for osteoarthritis include drug and surgical treatments. Drug treatment can successfully alleviate pain but not satisfactorily reverse joint damage, while surgical intervention is typically used to treat end-stage disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…ADSC and WJMSC are considered efficient cell sources for tissue engineering due to their good proliferative and differentiation capabilities, easiness of access and lack of ethical issues with their procurement. WJMSC of allogeneic origin are reportedly non-immunogenic, can generate clinically relevant number of mesenchymal progenitors and are already the object of clinical trials ( Liang et al, 2020 ). In this study we focused on comparing the two cell sources in respect to their capability to undergo chondrogenic lineage differentiation under magnetically delivered mechanical stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…ADSC and WJMSC are considered efficient cell sources for tissue engineering due to their good proliferative and differentiation capabilities, easiness of access and lack of ethical issues with their procurement. WJMSC of allogeneic origin are reportedly non-immunogenic, can generate clinically relevant number of mesenchymal progenitors and are already the object of clinical trials ( Liang et al, 2020 ). In this study we focused on comparing the two cell sources in respect to their capability to undergo chondrogenic lineage differentiation under magnetically delivered mechanical stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of experiments demonstrated that Wharton's jelly-derived mesenchymal stem cells (WJ-MSCs) are potential to differentiate into chondrocytes under appropriate stimulation and induction. Once this effect is aided by biologically active scaffolds, WJ-MSCs will be able to significantly promote the repair of articular cartilage damage in model animals (83), and this differentiation effect of WJ-MSCs is more durable and can significantly protect articular cartilage from being damaged for a long time (84,85). In addition, it was demonstrated that WJ-MSCs have superior cartilage regeneration ability compared with BM-MSCs.…”
Section: Umbilical Cordmentioning
confidence: 99%
“…TG-C is currently under FDA review with the potential to become the first cell and gene therapy in OA. Injectable mesenchymal stem cells (MSCs) have also drawn much attention, however the outcomes are controversial in OA [ 384 , 409 , 410 , 413 ]. This could possibly be due to the heterogeneity in MSC preparation and the subsets of OA patient included in the study (e.g., only older patients with knee OA).…”
Section: Neurological Diseasesmentioning
confidence: 99%